USA INVASION IN AFGHANISTAN AND ITS IMPACT ON CENTRAL ASIA - Zhekenov, Duman; Ahmadzai, Bakhtyar Gul (American International Journal of Social Science Research, 2023)
This study Examines the effects of the warfare in Afghanistan, which has resulted in immense casualties, change of political power. The political aspects of American presence in Afghanistan and its effects on the Central Asian region are the main subjects of our research. The goal of the study is to comprehend the complex relationship that emerged after 9/11 attacks and the American invasion. We use qualitative and descriptive-analytical techniques to evaluate the effects of American presence on the Central Asian nations. Our analysis focuses on assessing the effects on the economy, security, and sovereignty of the region. Afghanistan’s crucial role in determining the geopolitical dynamics of the area has an impact on Central Asia, which has historically served as a crossroads for world powers. Our finding address important issues pertaining to the strategic goals of the United States in Central Asia. We shed light on how they affect regional sovereignty, economy, and security. The dynamics of Afghanistan have continued to influence interactions and conflicts in Central Asia, magnifying the engagement of international and regional forces as well as the activity of fundamentalist groups. The stability of Central Asian nations is being put under further stress by the growth of extremism. In conclusion, our research reveals the complex interactions between American participation in Afghanistan and the stability and growth of Central Asia. We provide a comprehensive analysis of how the U.S. presence has impacted Central Asian dynamics, illuminating its wider security implications for the region and the world. JEL Classification Codes: N40.